Arginine-Based Poly(I:C)-Loaded Nanocomplexes for the Polarization of Macrophages Toward M1-Antitumoral Effectors - Dacoba, Tamara G.; Anfray, Clément; Mainini, Francesco; Allavena, Paola; Alonso, María José; Torres Andón, Fernando; Crecente-Campo, José (Frontiers in Immunology, 2020)
Background: Tumor-associated macrophages (TAMs), with M2-like immunosuppressive profiles, are key players in the development and dissemination of tumors. Hence, the induction of M1 pro-inflammatory and anti-tumoral states is critical to fight against cancer cells. The activation of the endosomal toll-like receptor 3 by its agonist poly(I:C) has shown to efficiently drive this polarization process. Unfortunately, poly(I:C) presents significant systemic toxicity, and its clinical use is restricted to a local administration. Therefore, the objective of this work has been to facilitate the delivery of poly(I:C) to macrophages through the use of nanotechnology, that will ultimately drive their phenotype towards pro-inflammatory states. Methods: Poly(I:C) was complexed to arginine-rich polypeptides, and then further enveloped with an anionic polymeric layer either by film hydration or incubation. Physicochemical characterization of the nanocomplexes was conducted by dynamic light scattering and transmission electron microscopy, and poly(I:C) association efficiency by gel electrophoresis. Primary human-derived macrophages were used as relevant in vitro cell model. Alamar Blue assay, ELISA, PCR and flow cytometry were used to determine macrophage viability, polarization, chemokine secretion and uptake of nanocomplexes. The cytotoxic activity of pre-treated macrophages against PANC-1 cancer cells was assessed by flow cytometry. Results: The final poly(I:C) nanocomplexes presented sizes lower than 200 nm, with surface charges ranging from +40 to -20 mV, depending on the envelopment. They all presented high poly(I:C) loading values, from 12 to 50%, and great stability in cell culture media. In vitro, poly(I:C) nanocomplexes were highly taken up by macrophages, in comparison to the free molecule. Macrophage treatment with these nanocomplexes did not reduce their viability and efficiently stimulated the secretion of the T-cell recruiter chemokines CXCL10 and CCL5, of great importance for an effective anti-tumor immune response. Finally, poly(I:C) nanocomplexes significantly increased the ability of treated macrophages to directly kill cancer cells. Conclusion: Overall, these enveloped poly(I:C) nanocomplexes might represent a therapeutic option to fight cancer through the induction of cytotoxic M1-polarized macrophages.